Down-Regulation of MiR-181c-5p Promotes Epithelial-to-Mesenchymal Transition in Laryngeal Squamous Cell Carcinoma via Targeting SERPINE1 - Li, Xin; Wu, Ping; Tang, Yaoyun; Fan, Yuhua; Liu, Yalan; Fang, Xing; Wang, Wei; Zhao, Suping (Frontiers in Oncology, 2020)
Laryngeal squamous cell carcinoma (LSCC) arises from the squamous epithelium of the larynx and is associated with a high incidence of cervical lymph node metastasis. MicroRNAs (miRNAs) play a crucial role in the epigenetic regulation of cellular biological processes, including cancer metastasis. However, the molecular mechanisms of specific miRNAs responsible for LSCC metastasis and their clinical significance have yet to be fully elucidated. In this study, LSCC cohort datasets from the Gene Expression Omnibus (GEO) and The Cancer Genome Atlas (TCGA) were downloaded and examined by comprehensive bioinformatics analysis, which revealed that upregulation of mRNA SERPINE1 and downregulation of miR-181c-5p were associated with unfavorable overall survival. Our analysis showed that SERPINE1 expression negatively correlated with the expression level of miR-181c-5p in our LSCC patient samples. Silencing of miR-181c-5p expression promoted cell migration and invasion in cell lines, whereas the overexpression of miR-181c-5p suppressed cell migration and epithelial-to-mesenchymal transition (EMT) through the downregulation of SERPINE1. Further analysis showed that the enhancement effect on EMT and metastasis induced by silencing miR-181c-5p could be rescued through knockdown of SERPINE1 expression in vitro. Collectively, our findings indicated that miR-181c-5p acted as a EMT suppressor miRNA by downregulation of SERPINE1 in LSCC and offers novel strategies for the prevention of metastasis in LSCC.